Reconsidering the paradigm “death” form transhumanism: Will death remain only and illusion? - Capone, Nadia; Albert Márquez, José J. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The transcience of existence, the fragility of life and human transcience do nothing but remind each of us of the imminence of death, now experienced as an unparalleled tragedy, accompanied, often, by the anguish of witnessing a slow and gradual ageing of the body. In the post-modern era characterized by pervasive technology, a new religion is emerging that aims to halt the ageing process and defeat death once and for all. But what is the price to be paid: according to some, we will witness the dissolution of the human being’s soul; according to others, the world will be populated by humanoids with severe psychic problems.